Individual Educational Paths in the Universities of Russia and Great Britain: Theoretical Aspects - N. Y. Shaposhnikova (Vestnik MGIMO-Universiteta, 2015)
The author of the article points out that the Federal Law on Education and FSES HPE of the third generation require that higher education institutions should form and realize students' individual educational paths in the learning process. The article presents an overview of the different approaches to the definition of the term "individual educational path". It also gives a brief overview of the existing terms in Russian sources, which are close in meaning to the term above. The author formulates her own tentative definition of the term "individual educational path" which is based on the analysis made. The article further addresses the solution to the problem of the individualization of higher education learning process in Great Britain, which is described through the term "Personal Development Planning". The meaning of the term is shown through the set of actions, which include: planning, doing things, recording the experience of self, reviewing and evaluating this experience, using the personal knowledge derived from reflection and understanding of self as well as the learning abilities of self to plan future actions. In conclusion, the meanings of the terms "individual educational path" and "Personal Development Planning" are compared. The author stresses the importance of studying Great Britain's experience - the practice of solving problems connected with the individualization of the university learning process and the possibilities to use it to facilitate the implementation of students' individual educational paths in Russian higher education institutions.